Green Investment Policy as Moderator of ESG and Profitability on Value Relevance in Indonesian Coal Firm - Rizaldi, Fredy; Arrozi, Muhammad Fachruddin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Growing sustainability awareness and regulatory pressure have encouraged coal companies to adopt ESG disclosure and green investment initiatives. However, empirical evidence on whether these practices enhance firm value remains inconclusive, particularly in emerging markets. Prior studies report inconsistent results regarding the value relevance of ESG disclosure and profitability, while the moderating role of Green Investment Policy (GIP) remains underexplored. Addressing this gap, this study examines the effect of ESG disclosure and profitability on the value relevance of accounting information, measured by Tobin’s Q, and investigates GIP as a moderating variable. Panel data were obtained from coal companies listed on the Indonesia Stock Exchange during 2019–2024 and analyzed using moderated regression analysis with robust standard errors. The findings reveal that ESG disclosure does not significantly affect firm value, either directly or when moderated by GIP. In contrast, profitability moderated by GIP shows a positive and significant effect, indicating that the market values profits more highly when they are strategically allocated to green investments. This study contributes to accounting and sustainability literature by demonstrating that green investment policy strengthens the value relevance of profitability, highlighting the importance of integrating financial performance with substantive sustainability strategies in carbon-intensive industries.